Incidence and outcomes of intraductal oncocytic papillary neoplasm-derived pancreatic cancer compared with tubular and colloid intraductal papillary mucinous neoplasm-derived pancreatic cancer: an international multicenter retrospective study - Habib, Joseph; Hidalgo Salinas, Camila; Berger, Natalie F.; Rompen, Ingmar F.; Campbell, Brady A.; Kinny-Köster, Benedict; Andel, Paul C. M.; Hewitt, D. Brock; Kaiser, Jörg; Billeter, Adrian T.; Perera, Rafael; Morgan, Katherine; et al. (Annals of surgical oncology, 2025)
Background: Intraductal papillary mucinous neoplasm (IPMN)-derived pancreatic cancer was previously categorized into tubular, colloid, and oncocytic subtypes. Intraductal oncocytic papillary neoplasms (IOPN) has long been associated with superior prognosis/indolent behavior, however, there is discordant emerging evidence. This study aimed to investigate this conflicting literature. Methods: Patients with resected IOPN-derived and IPMN-derived pancreatic cancer were identified from six international centers. Log-rank tests compared time to (TtR) and survival after (SAR) recurrence and five-year overall survival (OS). A multivariable mixed model was used to determine hazard ratios (HR) with confidence intervals (95%CI) for five-year survival. Results: Of 879 patients, 20 (2%) had IOPN-derived pancreatic cancer. Most patients had T1 (55%) or N0 (70%) disease. IOPN and colloid IPMN-derived pancreatic cancers had similar recurrence rates (25% vs. 24%), while recurrence was more common in tubular IPMN-derived pancreatic cancer (42%, p < 0.001). IOPN-derived pancreatic cancer displayed a longer TtR and SAR compared to colloid and tubular IPMN-derived pancreatic cancers. IOPN-derived and colloid IPMN-derived cancers demonstrated significantly lower 5-year mortality risks compared to tubular IPMN-derived cancers (74% and 27% risk reduction, respectively; p < 0.05). Conclusion: IOPN-derived pancreatic cancers have excellent OS. However, some patients have poor prognostic factors and are at risk for both local and systemic recurrence. Given more indolent disease progression given delayed TtR and prolonged SAR compared to colloid and tubular IPMN-derived pancreatic cancers, there may be a role for prolonged surveillance.
Online veröffentlicht: 19. Juli 2025
Gesehen am 26.11.2025